(untitled) (Jóvenes en la Ciencia, 2026)
Rabbit meat stands out for its high nutritional value and profitability due to low production costs and feed efficiency. Despite benefits such as combating malnutrition and potential in healthy markets, it faces unresolved challenges over the years, including social stigma and low cultural acceptance, leading to low consumption and, consequently, small-scale production. The objective of this study is to identify limitations, areas for improvement, and opportunities to position rabbit meat in international markets, contributing to food security and profitability. Using information from official sources and a SWOT analysis, the current market is diagnosed, comparing it with successful cases in countries like Italy and Malta, to propose sustainable strategies for this market. This aims to increase demand, strengthen food security, and position Mexico in international trade through the rabbit meat sector.